2000
DOI: 10.1016/s0272-8842(00)00004-3
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanotubes in novel ceramic matrix nanocomposites

Abstract: International audienceNovel carbon nanotubes-metal-ceramic nanocomposite powders and dense materials have been prepared and their micro-structure and mechanical properties have been investigated. After a brief review on the structure, synthesis and physical properties of carbon nanotubes, we describe an original catalytic method that produces ceramic-matrix composite powders that contain in situ grown nanotubes. The synthesis parameters that favour the obtention of very high quantities of nanotubes are discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
182
1
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 379 publications
(190 citation statements)
references
References 14 publications
(18 reference statements)
5
182
1
2
Order By: Relevance
“…One of the first studies on synthesis of CNT/ceramic composites (published in two parts) was authored by Peigney and co-workers 39,40 [41][42][43][44][45][46][47][48] . These composite powders can then be hot pressed to form macroscopic composites.…”
Section: In-situ Growth Of Cnts By Chemical Vapour Decomposition (Cvd)mentioning
confidence: 99%
“…One of the first studies on synthesis of CNT/ceramic composites (published in two parts) was authored by Peigney and co-workers 39,40 [41][42][43][44][45][46][47][48] . These composite powders can then be hot pressed to form macroscopic composites.…”
Section: In-situ Growth Of Cnts By Chemical Vapour Decomposition (Cvd)mentioning
confidence: 99%
“…Reaction (4) can only occur after reaction (3) is completed and enough O 2 has been produced by reaction (5). Consequently, (4) takes place if CA is defective.…”
Section: Citric Acid Combustion (Powders Ca05 Ca1 and Ca2)mentioning
confidence: 99%
“…3 This method, which obviates any mixing step, is particularly interesting for the subsequent preparation of dense oxide-matrix composites with a very homogeneous dis-tribution of the CNTs. [4][5][6] It has been shown that the starting solid solution for CNT production must be crystallised in the corundum form 7 and that a partitioning into two phases, ␣-Al 2 O 3 rich (␣ 1 ) and ␣-Fe 2 O 3 rich (␣ 2 ), respectively, must be avoided. 8 Moreover, to optimise the amount of CNTs, a maximum iron content in the single-phase oxide is desirable.…”
Section: Introductionmentioning
confidence: 99%
“…Even in composites a very small amount of CNTs can induce significant changes in the material's properties. At present much work continues on the development of CNTs reinforced polymer, ceramic and metal matrix composites (Peigney et al 2000;Ning et al 2003;Qiu et al 2003). However, very little work is carried out on carbon-reinforced carbon composites (Gao et al 2005;Song et al 2007;Song et al 2008).…”
Section: Introductionmentioning
confidence: 99%